PERBANDINGAN KEKAKUAN PUNTIR (TORSIONAL STIFFNESS) ANTARA BALOK KAYU KAMPER BERPENAMPANG HOLLOW (BOX BEAM) DAN SOLID - Handika Setya Wijaya; Blima Oktaviastuti (Reka Buana : Jurnal Ilmiah Teknik Sipil dan Teknik Kimia, 2017)
Indonesia is one of ten countries which the largest wood producer in the world. Wood is one of green materials if it’s compared with concrete and steel material. Wood is renewable material too. The problem of using wood for building construction is less of wood with large section dimension. So, engeenered wood appear to solve this problem. One of engeenered wood types is box beam. Box beam can increase inertia of material if it’s compared to traditional wood beam with same section dimension area. The purpose of this experiment is to know the comparasion about torsional stiffness between wood box beam and wood traditional beam. The result of this experiment show that Beam 1 (T.40.40) or traditional beam have torsional stiffness about 105,90 kg.m/rad. Beam 2 (T.45.45.12) is about 159,69 kg.m/rad. Beam 3 (T.50.50.10) is about 190,22 kg.m/rad. And at last, Beam 4 (T.58.58.8) is about 252,89 kg.m/rad. From the result, there are linier chart relationship between torsional stiffness and ratio of wall thickness and section dimension of box beam (t/a). The aplication of box beam should be developed. We hope box beam can be aplicated by people beacause torsional stiffness of box beam is larger than traditional wood beam exactly.